Methane losses from different biogas plant technologies. (15th February 2023) - Wechselberger, Viktoria; Reinelt, Torsten; Yngvesson, Johan; Scharfy, Deborah; Scheutz, Charlotte; Huber-Humer, Marion; Hrad, Marlies
Highlights: A harmonized on-site approach was used to investigate 33 European biogas plants. Component-specific methane emission factors (EFs) ranged between < 0.01 and 3.0 %. A dataset was provided containing 294 data points on technology specific emissions. Review of IPCC default EFs indicated over- and underestimation of sector emissions. Abstract: Biogas and biomethane production can play an important role in a fossil-fuel-free energy supply, provided that process-related methane (CH4 ) losses are minimized. Addressing the lack of representative emission data, this study aims to provide component specific CH4 emission factors (EFs) for various biogas plant technologies, enabling more accurate emission estimates for the biogas sector and supporting the identification of low emission technologies. Four measurement teams investigated 33 biogas plants in Austria, Germany, Sweden and Switzerland including mainly agricultural and biowaste treating facilities. For the first time, a harmonized measurement procedure was used to systematically survey individual on-site emission sources and leakages. Measurements revealed a large variability in technology specific emissions, especially for biogas utilization and upgrading. Median loss from combined heat and power (CHP) plants was 1.6 % for gas engines (n = 21), and 3.0 % for pilot injection units (n = 3) of the input CH4 . Biogas upgrading units showed median CH4 slips of < 0.1 % (chemical scrubbers, n = 4), 0.1 % (after exhaust gas treatment, n = 3) and 2.9 % (water scrubbers, n = 2). Not-gastight digestate storage (n = 8) was identified as a major emission source with maximum 5.6 % of the produced CH4 emitted. Individual leakages (n = 37) released between 0.0 and 2.1 % (median 0.1 %) relative to the CH4 production. All measurement and secondary data are provided in a harmonized dataset (294 datapoints). A review of IPCC default EFs indicate an underestimation of emissions from biogas utilization (reported in the energy sector) while the impact of leakages on overall plant emissions (waste sector) may be overestimated for European biogas plants.